RESPIRATORY ORGANS CLINICAL LABORATORY DIAGNOSTICS LITERATURE REVIEW - Berdiyarova Shokhida Shukurullayevna; Bakirov Asadullo Abdiqodirovich (Web of Journals Publishing, 2024)
This article gives us the opportunity to consider the main methods, object and features of laboratory diagnostics of diseases of the respiratory system. The structure of the lungs provides the function of gas exchange. In the study of the anatomical structure of the lungs, it is necessary to give special attention to the study of gas exchange in the lungs (study of its activity at the cell level). Microscopic examination of sputum is relevant in the diagnosis and diphdiagnostics of most diseases.
Keywords: Lungs, sputum, breathing, diagnostics, laboratory, elastic fibers, differential diagnosis.